DISTRIBUSI ZAKAT UNTUK KESEJAHTERAAN: STUDI PADA LAZ YATIM MANDIRI SURABAYA - Moch. Irfansyah; Moh. Romdlon Izzul Haq; Ziyanatun Nafisah; Erinda Kusuma Dayanti; Lilik Rahmawati (Nurul Jadid University, 2020)
Zakat is a worship required by Allah SWT for every Muslim and zakat is included in the third pillar of Islam which is paying zakat. There is two kinds of zakat namely zakat soul (zakat fitrah) and zakat treasure (zakat maal). This study aims to find out how the management of zakat is carried out by one of the national amil zakat institutions, namely yatim mandiri in Surabaya. This research uses a qualitative method by observing one of the national amil zakat institutions (yatim mandiri). In this study, we researching how zakat management starts from how to get zakat funds then distributing zakat funds to the community, financial management with in the zakat institution, then the programs owned by the amil zakat institutions to the management of all zakat funds so that can make people who are less fortunate.